2018
DOI: 10.1080/09513590.2018.1463362
|View full text |Cite
|
Sign up to set email alerts
|

Complete remission of cerebral endometriosis with dienogest: a case report

Abstract: The most recent evidences suggest the use of progesterone mimicking drugs for the treatment of endometriosis. Particularly, dienogest has been largely tested. However, the standard treatment of extra-pelvic endometriosis is debated. Particularly, cerebral localization of endometriosis is a very rare clinical condition. The surgical approach for such a particular disorder would consist in difficult procedures, thus leading to prefer the medical treatment. We hereby report the clinical case of a cerebral localiz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
15
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 23 publications
0
15
0
Order By: Relevance
“…18,19 Two histologically confirmed cases of cerebral endometriosis have been reported: one in 1987 by Thibodeau et al 19 and one in 1993 by Ichida et al 17 There is a third case of catamenial epilepsy with presumed cerebral endometriosis. 20 A fourth case was published in 2018 by Maniglio et al 21 The correct treatment for cerebral endometriosis is unknown. The only published case of cerebellar endometriosis is from 2004.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…18,19 Two histologically confirmed cases of cerebral endometriosis have been reported: one in 1987 by Thibodeau et al 19 and one in 1993 by Ichida et al 17 There is a third case of catamenial epilepsy with presumed cerebral endometriosis. 20 A fourth case was published in 2018 by Maniglio et al 21 The correct treatment for cerebral endometriosis is unknown. The only published case of cerebellar endometriosis is from 2004.…”
Section: Discussionmentioning
confidence: 99%
“…26 A case report published by Maniglio et al in 2018 showed remission of cerebral endometriosis after Dienogest treatment. 21 Dienogest is currently the only drug showing documented improvement of central nervous system endometriosis without surgical intervention.…”
Section: Discussionmentioning
confidence: 99%
“…So, we believe COCs could be the first choice for long term use in these patients. Recently, there were reports of Dienogest in the TES patient recurrent after surgery [4] and the patient with cerebral endometriosis [15].…”
Section: Discussionmentioning
confidence: 99%
“…The most common anatomical location of endometriosis is pelvic cavity, and it is rarely found in extra pelvic cavity [13]. The extragenital endometriosis represents 5-12% of endometriosis [1,2] and has been reported in multiple organ and systems, such as urinary tract [14], brain [15], gastrointestinal tract [16] and lungs. Though the prevalence of endometriosis is around 15% [17], the extragenital endometriosis represents 5% of the localizations [1], and the TES is very rare [13], and it is even rarer to have TES with catamental hemoptysis as the main clinical manifestation, so the prevalence and etiology of thoracic endometriosis is unknown as most data comes from simple case reports or short series [13].…”
Section: Introductionmentioning
confidence: 99%
“…However, data research of medical literature supporting this diagnosis shows a small number of studies and the specific research on medline led to the finding of only four case reports. 14…”
Section: Introductionmentioning
confidence: 99%